Monitoring changes in land-use practices following agrarian de-collectivisation in Ethiopia - Omiti, J.M.; Parton, K.A.; Sinden, J.A.; Ehui, Simeon K. (Elsevier, 1999)
Since 1975, agricultural land tenure arrangements in Ethiopia have changed from a feudal system, to a socialist model with semi-collectivist villages and, from 1991, to a small-holder system based on private (freehold) ownershiBy surveying a random sample of 94 households in the Ethiopian highlands, the paper examines (a) how de-collectivisation has affected important parts of the agrarian structure such as land tenure and common property and (b) the subsequent responses of farmers in terms of their land-use practices. The results provide some grounds for optimism that the freeing-up of the land market will bring with it more sustainable land-use practices.